Robust Digital Images Watermarking Technique Based on Eigenvectors - Jalil, Alyaa Jaber (Journal of College of Education, 2021)
The growth of new imaging technologies has created a need for techniques that can be used for copyright protection of digital images. In this paper, a new and robust spread spectrum based watermarking scheme has been proposed. The proposed scheme depend on both Discrete Wavelet Transform (DWT) and Discrete Cosine Transform (DCT). First, we decompose the image by DWT into a single level. Then, the approximation part is divided into blocks. The embedding is done in an adaptive fashion depending on the Eigenvalues (Ev) of the block. A chaotic sequence of real numbers, depends on a secret key, is embedded as a watermark in the DCT coefficients of the selected blocks. Detection stage generates a watermark which would be compared with the original watermark, by the correlation measure, to determine the existing of the watermark or not. Different tests have been experimented to explain the transparency and the robust of the proposed scheme.